Revenue Sharing and Absolute League Quality; Talent Investment and Talent Allocation. (February 2015) - Kesenne, Stefan
Abstract Beside the competitive balance or the relative quality of teams in a sports league, also a league's absolute quality matters to attract spectators. If the absolute quality depends among other variables, on the total budget of the league, it can be shown that that revenue sharing enhances the absolute quality by improving the allocation of talent over the teams in both a profit‐ and a win‐maximisation league, even if it worsens the competitive balance.